The Study of urban viability indicators status in Shahrekord, based on the position of urban management - pezhman mohamadi (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study is to investigate the status of urban viability indicators in Shahrekord, based on the position of urban management. Research in terms of purpose (type of use) is an applied research. The method used in this research is a descriptive-analytical method. The statistical population of this study is Shahrekord residents, and the statistical area of ​​the whole area is located in Shahr-e-Kord. The number of statistical population is equal to (160,000). The sample size was 383 people, determined according to the Cochran formula and available randomly. The collected data were analyzed by AMOS and TES and Friedman tests using SPSS software and structural equation path analysis. The results show that based on the analysis of the path of structural equations of urban management, the social index, with a coefficient of 0.22, on the economic index, with a coefficient of 0.85, and on the environmental index, with a coefficient of 0.30. have been. Accordingly, the economic index has the most impact, and the social indicator has the lowest impact. Based on the T test, the economic index is in the best position, followed by the management index, the social index, and the last rank of the environmental index. According to the Friedman test, the first rank index, the social index ranked second, and the environmental index ranked third.